Utility of Ultraportable Echocardiography in the Preoperative Evaluation of Noncardiac Surgery - Costa,Jean Allan (2016)
Abstract Background: The ultraportable echocardiogram machine, with relevant portability and easiness in performing diagnoses, when in experienced hands, may contribute to the reliability of preoperative evaluation in noncardiac surgeries. Objectives: To assess cardiac function parameters in patients aged older than 60 years, candidates of elective noncardiac surgeries, classified as ASA1 or ASA 2 according to surgical risk. Methods: A total of 211 patients referred for elective surgeries, without suspicion of previous heart diseases, were included in the study. Assessment of patients was conducted by conventional echocardiogram using the ultraportable V Scan (GE) device right after the pre-anesthetic clinical evaluation. We assessed the clinical impact of echocardiography results by using a questionnaire addressed to the anesthetist. Results: Mean age of patients was 68.9 ± 7.0 years, 154 were women. The most frequent surgeries were: a) facectomy - cataract - 18; b) inguinal hernia surgery - 18; c) Cholecystectomy - 16. We found 58 normal tests (27.5%), 70 (33.2%) with mild valve reflux, and 83 (39.3%) with relevant abnormality, such as increase in heart chamber size, global and/or segmental contractile dysfunction, significant valve dysfunction or other unspecified. Test results caused delay of surgical procedure for a more detailed cardiac evaluation in 20 (9.5%) patients, and change in anesthetic management in 7 (3.3%). Conclusion: There was a considerable clinical impact with the use of the ultraportable echocardiography, since one out of every ten patients evaluated had their clinical management changed due to the detection of previously unsuspected, significant heart diseases, with the potential for severe complications.